Numerical investigation on pile group efficiency embedded in soft clay. (14th December 2020) - Ferchat, Abdelkrim; Houhou, Mohamed Nabil; Benmebarek, Sadok
Abstract : Purpose: This paper aims to investigate the pile group efficiency based on the load-settlement response in soft clay conditions, considering several pile configurations using a variable number of piles and pile spacing. The overall objective of the present paper is to provide further insight into the mechanical response of the pile group and aim at helping the engineers in taking a logical path in an iterative design process for pile group efficiency. Design/methodology/approach: To investigate the pile group efficiency, three-dimensional (3D) numerical simulations were performed using the finite-difference code FLAC3D. Findings: The obtained numerical results are validated by comparing them to those of similar subgrade structure and in comparable geological conditions provided within the literature. The results indicated that although the bearing capacity of the pile group increases with increasing number of piles, the efficiency of the pile group is very important for a small number of piles. However, increasing of pile spacing has a positive effect on pile group efficiency depending on piles number and settlement level. The pertinence of the 3D numerical results of efficiency coefficient is judged by comparison with those obtained from the most popular formulas available in the literature. Originality/value: A predicted model is also proposed which is validated with the obtained numerical results to a better goodness of fit.